Maternal segregation of the Dutch preeclampsia locus at 10q22 with a new member of the winged helix gene family - van Dijk, Marie; Mulders, Joyce; Poutsma, Ankie; Könst, Andrea A M; Lachmeijer, Augusta M A; Dekker, Gustaaf A; Blankenstein, Marinus A; Oudejans, Cees B M (Nature genetics, 2005)
Preeclampsia is a pregnancy-associated disease with maternal symptoms but placental origin. Epigenetic inheritance is involved in some populations. By sequence analysis of 17 genes in the 10q22 region with maternal effects, we narrowed the minimal critical region linked with preeclampsia in the Netherlands to 444 kb. All but one gene in this region, which lies within a female-specific recombination hotspot, encode DNA- or RNA-binding proteins. One gene, STOX1 (also called C10orf24 ), contained five different missense mutations, identical between affected sisters, cosegregating with the preeclamptic phenotype and following matrilineal inheritance. Four STOX1 transcripts are expressed in early placenta, including invasive extravillus trophoblast, generating three different isoforms. All contain a winged helix domain related to the forkhead (FOX) family. The largest STOX1 isoform has exclusive nuclear or cytoplasmic expression, indicating activation and inactivation, respectively, of the PI3K-Akt-FOX pathway. Because all 38 FOX proteins and all 8 STOX1 homologs have either tyrosine or phenylalanine at position 153, the predominant Y153H variation is highly mutagenic by conservation criteria but subject to incomplete penetrance. STOX1 is a candidate for preeclampsia controlling polyploidization of extravillus trophoblast.